STRATEGI PENGEMBANGAN USAH MIKRO, KECIL, DAN MENENGAH (UMKM) STUDI KASUS PADA TOKO MERDEKA SANGATTA KABUPATEN KUTAI TIMUR - Anwar Arifin (Tinta Nusantara 2018 Vol.1, 2022)
This research is qualitative research and survey research. The subjects of this research are consumers at the merdeka store in Kutai Regency. The results showed that: The main strength at the Merdeka Sangatta Store based on the highest score was the Price of Products Sold at the Merdeka Sangatta Store which was affordable among customers, the business capital spent in accordance with the profits obtained, prioritizing the quality of product materials with the same score of 0.58. The prices of products sold at Merdeka Sangatta Stores are affordable among customers, the business capital issued is in accordance with the profits obtained, prioritizing the quality of product materials has always been a top priority in Merdeka Sangatta Stores.